Trends and variations in the prescribing of secondary preventative cardiovascular therapies for non-ST elevation myocardial infarction (NSTEMI) in Malaysia - Venkatason, Padmaa; Zaharan, Nur Lisa; Ismail, Muhammad Dzafir; Wan Ahmad, Wan Azman; Mahmood Zuhdi, Ahmad Syadi (Springer, 2018)
Purpose: Information is lacking on prescribing of preventative cardiovascular pharmacotherapies for patients with non-ST elevation myocardial infarction (NSTEMI) in the Asian region. This study examined the prescribing rate of these pharmacotherapies, comparing NSTEMI to STEMI, and variations across demographics and clinical factors within the NSTEMI group in the multi-ethnic Malaysian population. Methods: This is a retrospective analysis of the Malaysian National Cardiovascular Disease Database-Acute Coronary Syndrome registry from year 2006 to 2013 (n = 30,873). On-discharge pharmacotherapies examined were aspirin, ADP-antagonists, statins, ACE-inhibitors, angiotensin-II-receptor blockers, and beta-blockers. Multivariate logistic regression was used to calculate adjusted odds ratio of receiving individual pharmacotherapies according to patients’ characteristics in NSTEMI patients (n = 11,390). Results: Prescribing rates for cardiovascular pharmacotherapies had significantly increased especially for ADP-antagonists (76%) in NSTEMI patients. More than 85% were prescribed statins and antiplatelets but rates remained significantly lower compared to STEMI. Women and those over 65 years old were less likely to be prescribed these pharmacotherapies compared to men and younger NSTEMI patients. Chinese and Indians were more likely to receive selected pharmacotherapies compared to Malays (main ethnicity). Geographical variations were observed; East Malaysian (Malaysian Borneo) patients were less likely to receive these compared to Western region of Malaysian Peninsular. Underprescribing in patients with risk factors such as diabetes were observed with other co-morbidities influencing prescribing selectively. Conclusion: This study uncovers demographic and clinical variations in cardiovascular pharmacotherapies prescribing for NSTEMI. Concerted efforts by policy makers, specialty societies, and physicians are required focusing on elderly, women, Malays, East Malaysians, and high-risk patients.